Answer:
ther are two solutions
1. x = -5
2. x = -12
Step-by-step explanation:
-60 + -1 = -61
-30 + -2 = -32
-20 + -3 = -23
-15 + -4 = -19
-12 + -5 = -17
-10 + -6 = -16
-6 + -10 = -16
-5 + -12 = -17
-4 + -15 = -19
-3 + -20 = -23
-2 + -30 = -32
-1 + -60 = -61
1 + 60 = 61
2 + 30 = 32
3 + 20 = 23
4 + 15 = 19
5 + 12 = 17
Step-3 : Rewrite the polynomial splitting the middle term using the two factors found in step 2 above, 5 and 12
x2 + 5x + 12x + 60
Step-4 : Add up the first 2 terms, pulling out like factors :
x • (x+5)
Add up the last 2 terms, pulling out common factors :
12 • (x+5)
Step-5 : Add up the four terms of step 4 :
(x+12) • (x+5)
Which is the desired factorization
the two solutions are:
x =(-17+√49)/2=(-17+7)/2= -5.000
or:
x =(-17-√49)/2=(-17-7)/2= -12.000